2017
DOI: 10.1038/sj.bdj.2017.33
|View full text |Cite
|
Sign up to set email alerts
|

The interdisciplinary management of hypodontia patients in the UK: a national service evaluation

Abstract: Objective To examine the distribution of interdisciplinary clinics for hypodontia patients in the UK and to assess the provision of orthodontic-restorative care for hypodontia patients in units where this service is and is not available.Design Prospective, online-questionnaire.Setting Hospital orthodontic departments in the UK.Participants In total, consultants from 92 orthodontic departments completed the questionnaire.Methods Orthodontic consultants were asked to complete a questionnaire regarding the provis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…In such cases, the stability of positive effect after diagnostics and treatment is often rather low, and there is an increase in the rate of recurrence of orofacial pain and manifestations of the TMJ dysfunction. 4,23,24 An increasing number of authors believe that introduction of diagnostics and treatment methods based on modern methodologies is important in the treatment of this category of patients. 13,21 This was confirmed by the results of our study, which have demonstrated that the application of the complex interdisciplinary approach to prosthodontic rehabilitation contributes to the fact that statistically significantly lower (relative to the control group) levels of severity of pain during palpation of muscles of the masticatory organs, pain during opening the mouth and chewing, as well as indicators of visual analogue scale of assessment of painful sensations are observed in full-mouth reconstruction patients 1 to 3 years after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In such cases, the stability of positive effect after diagnostics and treatment is often rather low, and there is an increase in the rate of recurrence of orofacial pain and manifestations of the TMJ dysfunction. 4,23,24 An increasing number of authors believe that introduction of diagnostics and treatment methods based on modern methodologies is important in the treatment of this category of patients. 13,21 This was confirmed by the results of our study, which have demonstrated that the application of the complex interdisciplinary approach to prosthodontic rehabilitation contributes to the fact that statistically significantly lower (relative to the control group) levels of severity of pain during palpation of muscles of the masticatory organs, pain during opening the mouth and chewing, as well as indicators of visual analogue scale of assessment of painful sensations are observed in full-mouth reconstruction patients 1 to 3 years after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Application of such approach determines the necessity to apply methods of functional and imaging diagnostics, making it possible to perform quantitative and qualitative analysis of systems involved in the pathological process and develop a system of treatment and rehabilitation with subsequent quantitative and qualitative analysis of its effectiveness. 4,18 Thus, the problem of improving the results of rehabilitation of patients with various types of occlusion problems becomes highly relevant. At the same time, function of the masticatory system is an essential component of proper quality of human life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,9 Assessing the condition of the dentition, in general, and the TMJ, in particular, when examining a patient, one should take into account not only the history and clinical manifestations but also analyze the complex of anthropometric and functional parameters obtained using appropriate diagnostic methods. 10,13,22 Today, most authors consider occlusive disorders as potential factors in the development of functional disorders in the TMJ. [12][13][14][15] Thus, when performing a set of measures for the correction and restoration of the anatomical shape of the teeth, one of the key areas should be the correction of the pathology of the TMJ.…”
Section: Discussionmentioning
confidence: 99%
“…As part of a comprehensive interdisciplinary approach to diagnosis, it is necessary to use diagnostic research methods with the appropriate evidence base to verify the predominance of neuromuscular or occlusal-articular syndromes, as well as assess their systemic effect on the biomechanics of the musculoskeletal system. 5,7,22 Currently, several conservative methods for correcting joint disorders have been proposed. In clinical practice, selective grinding, acupuncture, therapeutic exercises, autogenic training, and physiotherapeutic procedures are actively used.…”
Section: Introductionmentioning
confidence: 99%